The relationship between sexual myths and intercultural sensitivity in university students - Cirban Ekrem, Ebru; Kurt, Aylin; Onal, Yakup; Ekrem, Ebru Cirban; Kurt, Aylin (Wiley, 2022)
Purpose In the study, it was aimed to investigate the relationship between sexual myths and intercultural sensitivity in university students. Method The study designed as cross-sectional research was carried out with the participation of 1,061 university students. Data collection tools used were the Personal Information Form, Sexual Myths Scale, and Intercultural Sensitivity Scale. Findings It was determined that the students believed in myths at a moderate level. The students who thought that being together with different cultures did not have a positive contribution were found to believe in sexual myths at a higher level (p < 0.001). It was also determined that intercultural sensitivity was a significant predictor of sexual myths in university students (p < 0.001). Implications for Practice While planning sexual education provided to relay sexual knowledge to societies accurately, cultural differences should be considered.
Keywords: Cultural Sensitivity; Sexual Myths; University Students